Knocking down Sterol regulatory element binding protein 2 (SREBF2) inhibits the Serine Protease 8 (PRSS8) /sodium channel epithelial 1alpha subunit (SCNN1A) axis to reduce the cell proliferation, migration and epithelial-mesenchymal transformation of ovarian cancer - Chunyan Cai (Taylor & Francis Group, 2021)
The pathogenesis of ovarian cancer (OC) is complex. Serine Protease 8 (PRSS8) is a potential biomarker for early detection of OC. Multiple databases were used to predict the expression of PRSS8, Sterol regulatory element binding protein (SREBP) and sodium channel epithelial 1alpha subunit (SCNN1A) in OC patients and to detect the relationship among the three. The expressions of PRSS8, SREBF2, SCNN1A and related factors of the pathway were detected by RT-qPCR and Western blot. The cell transfection was used to overexpress or inhibit the expression of PRSS8 and SREBF2, so as to explore its mechanism. MTT assay and Colony formation assay were used to detect cell proliferation. The Transwell and Wound Healing assays were utilized to measure cell invasion and migration. We have further confirmed cell-level studies in animals. We found that PRSS8 expression was up-regulated in OC patients and cell lines. Knocking down PRSS8 reduced the proliferation, migration and epithelial-mesenchymal transition (EMT) of OC cells, which was realized by SREBF2 transcriptional regulation. Knocking down SREBF2 reduced PRSS8 and then inhibited the expression of SCNN1A, thus affecting the proliferation, migration and EMT of OC cells. These results also applied to animals experiments. In conclusion, SREBF2 activates the PRSS8/SCNN1A axis to accelerate cell proliferation, migration and EMT of OC.